Synthesis of AuPt Bimetal and its Catalytic Properties in Ethanol Electrooxidation Reaction - Chika Shafa Maura; Mila Alawiyah; Sukro Muhab (Chemistry and Materials, 2024)
AuPt Bimetal has been successfully synthesized by electrodeposition method with potentiostat technique. By varying the concentration of Au ions in the solution they are able to control the morphology and composition of the synthesized sample. The morphology obtained from the AuPt synthesis is cauliflower. The effect of Au ion concentration in solution on the catalytic performance of AuPt, the greater the Au concentration, the greater the current density in the electrooxidation reaction. In addition, the concentration of Au ions in the solution affects the results of the deposition of Au and Pt elements. In the study of AuPt nanocatalysts with a 0.4 mM Au ion concentration in an electrolyte solution, it was shown to have good catalytic activity in the ethanol electrooxidation reaction, with the resulting current densities and If/Ib of 10.1 mA/cm2 and 43.53 mA/cm2, respectively. This is an implication of many Au compositions which are known to have the ability to absorb and oxidize CO to encourage an increase in current density and increase its catalytic activity.